Anatomical variations of radial artery and its morphology with clinical implications - Mukherjee, Barnali; Sarkar, Amita; Samanta, Shubhrangsu; Kannabathula, Ajay Babu (International Journal of Research in Medical Sciences, 2022)
Background: The radial artery (RA) is a continuation of the brachial artery and is one of the major blood supplying vessels to the structures of the forearm. It is originated in the cubital fossa at the level of the neck of the radius. It runs on the lateral aspect of the forearm before it reaches the wrist and branches out to supply the hand. The RA is also important clinically due to its location at the wrist, as it can be felt as a pulse and can be used to determine the heart rate. It is the artery of choice for coronary artery angiography, percutaneous coronary artery intervention, cannulation, and others. The main objective of this study is to study the variation in origin and course of the RA in cadavers. Methods: The present study was conducted with 100 upper limbs of 50 cadavers in the department of anatomy, Gouri devi institute medical sciences and hospital, Durgapur, West Bengal over a period of 2 years. By conventional dissection method, the axillary region, arm, forearm, and hand of each limb were dissected to clarify the course and branches of the RA. This anatomical descriptive study was conducted after approval of the ethical committee. The study period was March 2018 to August 2020. Results: RA took high origin from the brachial artery in arm is 6.66%. The maximum length was measured was 23.7 cm, minimum length was 18 cm and the mean value is 21.25. The RA after giving its branches continued in the forearm. In 96.88%, RA arose normally in cubital fossa. Conclusions: The anatomy and morphology of RA have many documented variations. Radiologist and surgeons should have a good understanding of normal morphological variations of RA.